ROUTING ALGORITHM OF THE FAMILY OF Q-ROUTING, BASED ON DYNAMIC CHANGES OF LEARNING RATES ACCORDING TO THE ESTIMATES OF THE AVERAGE DELIVERY TIME - Shilova, Yu.A. (Perm Federal Research Centre Journal, 2015)
One of the most urgent problems for mobile ad hoc network is the routing problem. A routing algorithm of the family of Q-Routing is developed and called Adaptive Rate Full Echo, and simulation of this algorithm has yielded good results. This algorithm is based on dynamic changes of learning rates according to estimates of the average network delay. The article also provides a brief overview of different routing protocols and algorithms, it provides a more detailed description of the basic algorithm of Q-Routing.